Hubungan Antara Kompaksi Tanah Dan Pertumbuhan Akar : Kajian Fisika Tanah Dalam Pertanian Berkelanjutan - Gulo, Lisna Juli Mawarni; Waruwu, Patricia Jenis Febriani (CV. SINAR HOWUHOWU, 2024)
Soil compaction is an important factor that affects root growth and crop productivity, especially in sustainable farming systems. This study aims to examine the relationship between soil compaction levels and corn root growth. Soil compaction treatments were applied at three levels: no compaction (control), moderate compaction, and high compaction. Parameters measured included root length, root volume, and root dry weight. The results showed that increasing soil compaction significantly reduced root growth, with high compaction resulting in shorter roots, smaller volume, and lower dry weight. In conclusion, high soil compaction limits root growth and affects the plant's ability to absorb water and nutrients. The implications of this study emphasize the importance of soil management practices that maintain porosity to support sustainable agriculture.